2007
DOI: 10.1007/s00415-006-0474-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between gray matter metabolic abnormalities and white matter inflammation in patients at the very early stage of MS

Abstract: Proton magnetic resonance spectroscopic imaging ((1)H-MRSI) was used to study metabolic abnormalities inside the gray matter (GM) during or distant to white matter (WM) inflammatory processes reflected by T(1) gadolinium-enhancing lesions in patients at the very early stage of multiple sclerosis (MS). The spectroscopic examination was performed in the axial plane using a home-designed acquisition-weighted, hamming shape, 2D-SE pulse sequence (TE = 135 ms; TR = 1,600 ms). Bilateral thalami and the medial occipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 54 publications
0
25
2
Order By: Relevance
“…Nevertheless, conventional MR imaging and consequently current MR imaging criteria do not sufficiently reflect special aspects of disease activity, in particular grey matter pathology which occurs abundantly in MS [41]. However, grey matter changes in MS can not be sufficiently visualized on conventional MR imaging techniques but may substantially contribute to metabolic changes (e.g.…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, conventional MR imaging and consequently current MR imaging criteria do not sufficiently reflect special aspects of disease activity, in particular grey matter pathology which occurs abundantly in MS [41]. However, grey matter changes in MS can not be sufficiently visualized on conventional MR imaging techniques but may substantially contribute to metabolic changes (e.g.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, whereas some studies have found statistically-significant correlations between cGM-NA and clinical status [42] and between cGM-NA/Cr and memory impairment in patients with MS, [46] other studies have failed to find statistically-significant correlations between cGM-NA and clinical disability in such patients [38,39,36,40,41,37]. It should be noted, however, that all of these studies had relatively-low sample sizes and some of them had a very limited range of cerebral WM-LL values [38,47] or scores on Kurtzke's Expanded Disability Status Scale [53] (EDSS) [38] -either of which would make it very difficult to find statistically-significant correlations. Thus, to the best of our knowledge, the relationship of 1 H-MRS(I) measures of cGM neuro-axonal integrity to cerebral WM-LL and clinical status in patients with MS has not yet been definitively established.…”
Section: The Relationship Of Cgm Pathology To Cerebral Wm Lesion-loadmentioning
confidence: 95%
“…With regards to the relationship between cerebral WM lesions and 1 H-MRS(I) measures of cGM pathology, Van Au Duong et al [47] studied cGM-NA/Cr values and cerebral WM inflammation in patients with CIS and found a significantly-lower mean NA/Cr value in the cGM of those 15 patients who had gadolinium-enhancing cerebral WM lesions than in the 25 patients who did not have any such lesions (and whose mean cGM-NA/Cr value did not differ from that of their normal controls). On the other hand, a number of 1 H-MRS(I) studies of cGM neuro-axonal integrity in patients with MS have failed to find statistically-significant correlations between cerebral WM lesion-load (WM-LL) and cGM-NA [38,40,37,44] or between cerebral WM-LL and cGM-NA/Cr [47]. Similarly, whereas some studies have found statistically-significant correlations between cGM-NA and clinical status [42] and between cGM-NA/Cr and memory impairment in patients with MS, [46] other studies have failed to find statistically-significant correlations between cGM-NA and clinical disability in such patients [38,39,36,40,41,37].…”
Section: The Relationship Of Cgm Pathology To Cerebral Wm Lesion-loadmentioning
confidence: 99%
See 1 more Smart Citation
“…On a more macroscopic scale, MS has been associated with diffuse brain hypoperfusion [16] and decreased cerebral metabolism [17] even in the initial stages of the disease [18]. Using dynamic susceptibility contrast-enhanced magnetic resonance imaging, Law et al [19] found significantly decreased cerebral blood flow (CBF) and significantly prolonged mean transit time throughout the normal appearing white matter (NAWM) in patients with relapsing-remitting MS. Adhya et al [20] also found significantly decreased CBF and cerebral blood volume (CBV) in NAWM regions of patients with either relapsingremitting or primary progressive MS compared with healthy subjects.…”
Section: The Hydrostatic Approachmentioning
confidence: 99%